2012
DOI: 10.1021/es203200d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity and Selectivity of Carbon Nanofiber Supported Pd Catalysts for Nitrite Reduction

Abstract: Pd-based catalyst treatment represents an emerging technology that shows promise to remove nitrate and nitrite from drinking water. In this work we use vapor-grown carbon nanofiber (CNF) supports in order to explore the effects of Pd nanoparticle size and interior versus exterior loading on nitrite reduction activity and selectivity (i.e., dinitrogen over ammonia production). Results show that nitrite reduction activity increases by 3.1-fold and selectivity decreases by 8.0-fold, with decreasing Pd nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 67 publications
4
104
5
Order By: Relevance
“…Actually, even with a much larger thickness at ~ 50 nm, Fe signal could still be detected by XPS on Previous studies had demonstrated that the reduction of mass transport limitation could also enhance the catalytic nitrite reduction activity and reduce the product selectivity to NH 4 + . 26,51 For example, D'Arino et al reported ܵ ேு ర శ could be depressed to 1.28% by the use of catalyst support with very low specific surface area and very few pore volume, 26 the reaction to bulk solution from its surface easily, and depressed pH gradient along pores effectively. All these characteristics of the Fe 3 O 4 @SiO 2 /Pd catalyst also contributed to its demonstrated high catalytic nitrite reduction activity without the detection of NH 4 + produced.…”
Section: Mass Transfer Limitation and Side Reactions During The Catalmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, even with a much larger thickness at ~ 50 nm, Fe signal could still be detected by XPS on Previous studies had demonstrated that the reduction of mass transport limitation could also enhance the catalytic nitrite reduction activity and reduce the product selectivity to NH 4 + . 26,51 For example, D'Arino et al reported ܵ ேு ర శ could be depressed to 1.28% by the use of catalyst support with very low specific surface area and very few pore volume, 26 the reaction to bulk solution from its surface easily, and depressed pH gradient along pores effectively. All these characteristics of the Fe 3 O 4 @SiO 2 /Pd catalyst also contributed to its demonstrated high catalytic nitrite reduction activity without the detection of NH 4 + produced.…”
Section: Mass Transfer Limitation and Side Reactions During The Catalmentioning
confidence: 99%
“…The material characterization results and the catalytic nitrite reduction performances of Fe 3 O 4 @SiO 2 /Pd catalysts with ~ 1%, 2.5%, and 5% Pd nanoparticle contents, respectively.Previous studies suggested that the N 2 selectivity was structure sensitive, and the selectivity to N 2 was enhanced with the increase of Pd nanoparticle size 12,51,55. Smaller Pd nanoparticles had more edges and corners, at which it was probably favorable for nitrite to undergo the deep hydrogenation to NH 4 + , while larger Pd nanoparticles had more flat terraces than smaller one and N 2 would be favorably formed on these sites due to their mild hydrogenation capability.21 In this study, however, no NH 4 + production was detected for all these Fe 3 O 4 @SiO 2 /Pd catalysts, although their Pd nanoparticle size and content were different.…”
mentioning
confidence: 99%
“…Nitrite concentrations after photocatalysis were measured by diazotization with sulfanilamide and coupling with N-(1-naphthyl)ethylene diamine (Korgel and Monbouquette 1997). Ammonia was measured by the salicylate method (Shuai et al 2012). UV absorbance was determined by a 722 UV-Vis spectrophotometer.…”
Section: Photocatalytic Activity Measurementsmentioning
confidence: 99%
“…Pd-catalytic reductive hydrodechlorination shows a promise for the remediation of CHCs, offering many advantages over other processes such as quick reaction, no halogenated intermediates and applicability for a broad range of reducible compounds (Agarwal et al, 2007;Knitt et al, 2007;Munakata and Reinhard, 2002;Shuai et al, 2012). Although it has been tested extensively in lab (Choe et al, 2010;Janiak and Okal, 2009;Zhu and Lim, 2007), large-scale treatments in the field are still limited because of the challenges such as H 2 supply and catalyst fouling (Chaplin et al, 2012b;Kopinke et al, 2004).…”
Section: Introductionmentioning
confidence: 99%